Clinical effectiveness of allopurinol–febuxostat versus allopurinol–colchicine combination therapy in patients with gout: A retrospective study at Universitas Sebelas Maret Hospital, Indonesia - Langgeng Inaya; Lucia Vita Inandha Dewi; Hidayah Apriliawan (Institute of Computer Science (IOCS), 2026)
Background: Gout is a metabolic disorder characterized by elevated serum uric acid levels, which may lead to joint inflammation and decreased quality of life. Combination therapies, including allopurinol–febuxostat and allopurinol–colchicine, are commonly used to control serum uric acid levels and improve clinical outcomes. Objective: This study aimed to compare the clinical effectiveness of allopurinol–febuxostat and allopurinol–colchicine combination therapy in patients with gout. Methods: This retrospective observational study used medical records of patients diagnosed with gout or hyperuricemia at Universitas Sebelas Maret Hospital. A total of 79 patients who met the inclusion criteria were included. Patient characteristics, serum uric acid levels before and after therapy, and follow-up duration were collected and analyzed using comparative statistical tests. Results: The allopurinol–febuxostat group showed a reduction in serum uric acid levels from 7.98 ± 0.50 mg/dL to 5.01 ± 0.53 mg/dL, corresponding to a mean reduction of 2.90 ± 0.62 mg/dL. The allopurinol–colchicine group showed a reduction from 7.98 ± 0.56 mg/dL to 5.24 ± 0.65 mg/dL, with a mean reduction of 2.83 ± 0.58 mg/dL. The between-group mean difference in serum uric acid reduction was 0.07 mg/dL, with a statistically significant difference in treatment effectiveness (p = 0.004). The 95% confidence interval (95% CI: [lower limit] to [upper limit]) and effect size (Cohen's d = [value]) should be reported to indicate the precision and magnitude of the treatment effect. Conclusion: Both combination therapies effectively reduced serum uric acid levels; however, the allopurinol–febuxostat combination demonstrated significantly greater effectiveness than the allopurinol–colchicine combination. Reporting confidence intervals and effect size alongside statistical significance provides a more comprehensive interpretation of the treatment effect.